Registered Replication Report on Srull and Wyer (1979). Issue 3 (September 2018) - McCarthy, Randy J.; Skowronski, John J.; Verschuere, Bruno; Meijer, Ewout H.; Jim, Ariane; Hoogesteyn, Katherine; Orthey, Robin; Acar, Oguz A.; Aczel, Balazs; Bakos, Bence E.; Barbosa, Fernando; Baskin, Ernest; et al.
Srull and Wyer (1979) demonstrated that exposing participants to more hostility-related stimuli caused them subsequently to interpret ambiguous behaviors as more hostile. In their Experiment 1, participants descrambled sets of words to form sentences. In one condition, 80% of the descrambled sentences described hostile behaviors, and in another condition, 20% described hostile behaviors. Following the descrambling task, all participants read a vignette about a man named Donald who behaved in an ambiguously hostile manner and then rated him on a set of personality traits. Next, participants rated the hostility of various ambiguously hostile behaviors (all ratings on scales from 0 to 10). Participants who descrambled mostly hostile sentences rated Donald and the ambiguous behaviors as approximately 3 scale points more hostile than did those who descrambled mostly neutral sentences. This Registered Replication Report describes the results of 26 independent replications ( N = 7, 373 in the total sample; k = 22 labs and N = 5, 610 in the primary analyses) of Srull and Wyer's Experiment 1, each of which followed a preregistered and vetted protocol. A random-effects meta-analysis showed that the protagonist was seen as 0.08 scale points more hostile when participants were primed with 80% hostile sentences than when they were primed with 20% hostile sentences (95% confidence interval, CI = [0.004, 0.16]). The ambiguously hostile behaviors were seen as 0.08 points less hostile when participants were primed with 80% hostile sentences than when they were primed with 20% hostile sentences (95% CI = [−0.18, 0.01]). Although the confidence interval for one outcome excluded zero and the observed effect was in the predicted direction, these results suggest that the currently used methods do not produce an assimilative priming effect that is practically and routinely detectable.